2021
DOI: 10.1002/jev2.12112
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles carry SARS‐CoV‐2 spike protein and serve as decoys for neutralizing antibodies

Abstract: In late 2019, a novel coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) emerged in Wuhan, China. SARS‐CoV‐2 and the disease it causes, coronavirus disease 2019 (COVID‐19), spread rapidly and became a global pandemic in early 2020. SARS‐CoV‐2 spike protein is responsible for viral entry and binds to angiotensin converting enzyme 2 (ACE2) on host cells, making it a major target of the immune system – particularly neutralizing antibodies (nAbs) that are induced by infection or vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 93 publications
(108 reference statements)
5
51
0
Order By: Relevance
“…Indeed, we deeply characterized at a single EV level the S-EVs showing variable co-expression of all three tetraspanins (CD9, CD63 and CD81) in about half of the isolated EVs, suggesting that the spike incorporated in a specific subset of EVs. This study parallels a recent study showing the neutralizing effect of spike carrying EVs obtained from HEK transfected cells [ 15 ]. The analysis of the obtained EGFP-bound spike EVs by nanoflow cytometry showed 85% of CD9 co-expression, whereas CD81 was mainly negative.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Indeed, we deeply characterized at a single EV level the S-EVs showing variable co-expression of all three tetraspanins (CD9, CD63 and CD81) in about half of the isolated EVs, suggesting that the spike incorporated in a specific subset of EVs. This study parallels a recent study showing the neutralizing effect of spike carrying EVs obtained from HEK transfected cells [ 15 ]. The analysis of the obtained EGFP-bound spike EVs by nanoflow cytometry showed 85% of CD9 co-expression, whereas CD81 was mainly negative.…”
Section: Discussionsupporting
confidence: 90%
“…This discrepancy could be due to the different sensitivity of the detection systems used. However, the authors showed that the spike protein was incorporated predominantly as the S2 subunit with rarer full-length glycoproteins [ 15 ]. At variance, in our study, we detected by western blot analysis mainly the full-length form of the spike protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Krishnamachary et al also found correlations between severity of the disease and EVs-associated proteins as well as EVs-mediated endothelial apoptosis [ 54 ]. EVs can also serve as decoys for neutralizing antibodies and modulate immunity [ 55 ]. A review article from Askenase focuses on the involvement of exosomes in convalescent plasma for COVID-19 therapy [ 56 ].…”
Section: Discussionmentioning
confidence: 99%